Evaluation of a new laryngoscope blade (Manipal throat packing blade) for throat pack insertion - D Muralikrishna; Anitha Nileshwar; Lokvendra Budania (Wolters Kluwer Medknow Publications, 2022)
Background and aims: Insertion of a throat pack using a Macintosh laryngoscope after placing an oral Ring, Adair and Elwyn (RAE) tube fixed to the lower lip in the midline invariably results in the lateral movement of the tongue or the tube requiring repositioning. The aim was to design a laryngoscope blade that would produce minimal movement of the endotracheal tube or the tongue during the insertion of throat pack and compare it with the Macintosh laryngoscope blade. Material and Methods: A laryngoscope blade similar to the Doughty's blade of Boyle Davis mouth gag with a groove in the center of the blade was initially designed. This was made of polyvinyl chloride to enable 3-D printing. Specifications given were modified after trial and error including addition of a flange. A bench study was then done to compare the Macintosh blade with the Manipal blade with and without flange. Forty anesthesia postgraduates and staff familiar with airway management inserted throat pack with each blade in random order in a manikin already intubated with an oral RAE tube and their impressions were noted. Results: The RAE tube remained in the midline after throat packing in 97.5 and 95% with Manipal blade with and without flange as compared to 52.5% with Macintosh blade. Ease of use was affected by the lack of sturdiness of the new blades. The light was good. Most people found both blades better or the same as the Macintosh blade. Conclusion: The Manipal laryngoscope blade with and without flange are both associated with the minimal lateral movement of the endotracheal tube and are easy to use. Their sturdiness must be improved.